MAXIMIZING INVENTOR’S PROFIT IN THE PROCESS OF INVENTION COMMERCIALIZATION BASED ON THE NORDHAUS MODEL - Lyashenko, Oksana (Journal of European Economy, 2017)
In this article, the author develops a model of inventor’s profit maximization in the process of commercializing an invention based on the critical analysis of the «optimal life of a patent» model offered by the American economist William Nordhaus. The author defines perspective directions for further modifications of the Nordhaus model for its application in the real economic conditions of Ukraine.